Electromagnetic wave shielding/absorption performances of cementitious composites incorporating carbon nanotube metamaterial with helical chirality. (October 2020) - Li, Linwei; Dong, Sufen; Dong, Xufeng; Yu, Xun; Han, Baoguo
Helical carbon nanotubes, a type of chiral metamaterial, were employed to investigate their effects as well as the mechanisms to electromagnetic wave shielding and absorption performances of cementitious composites over the frequency range from 2 GHz to 18 GHz. The results demonstrate that the best electromagnetic wave shielding effectiveness (SE) of cementitious composites filled with 7.5 wt.% helical carbon nanotubes is 1.39 times of that of cementitious composites without helical carbon nanotubes. The minimum reflectivity in 20 mm-thickness cementitious composites with 4.5 wt.% helical carbon nanotubes is 2.7 times of that of cementitious composites without helical carbon nanotubes. Cementitious composites with 7.5 wt.% helical carbon nanotubes have smallest matching thickness and the minimum reflectivity of −41.0 dB. By analyzing electromagnetic parameters and conductive mechanisms, it is found that helical carbon nanotubes mainly affect reflection loss ratio in electromagnetic wave shielding and the dielectric loss in electromagnetic wave absorption. Both parameters are attributed to the enhanced conductivity with the increase of helical carbon nanotubes. The percolation zone ranges from 1.5 wt.% to 7.5 wt.% for alternating current resistivity, with conductive path transferring from ion conduction to electron conduction as the content of helical carbon nanotubes increases. Additionally, incorporating helical carbon nanotubes essentially does not cause the decrease in compressive strength of cementitious composites. The results recommend that cementitious composites incorporating carbon nanotube metamaterial with helical chirality present high electromagnetic performances with satisfactory compressive strength.